Nepal : Development Policy Review, Restarting Growth and Poverty Reduction - World Bank (Washington, DC, 2012)
The report provides an assessment of Nepal's progress in development, and discusses the development policy agenda and priorities to accelerate development. The aim of the Development Policy Review (DPR) is to inform both on Government policies and further refinement of the country's poverty reduction strategy, as well as the Bank assistance and policy dialogue. It is based on the 10th Five Year Plan (2002-2007) and the Poverty Reduction Strategy Paper (PRSP), and, presents a menu of policies that address three related development themes. First, is the need to restart and accelerate growth mainly through commercializing agriculture, and increasing trade and competitiveness; second, is making growth more inclusive, by focusing on developing agriculture and the lagging Western regions; and, third, is improving governance and public service delivery by strengthening institutions at both the national and local government levels. However, implementing many policies will require a political consensus and mitigating, if not ending, the adverse effects o f the insurgency, and political discord among the principal actors. The review highlights the risks of an alternative scenario if a consensus is not reached, and the majority of the policies recommended are not implemented. Recommendations include: On economic management - improving high level monitoring of economic, trade, transport, and agricultural performance, with the inclusion of the private sector; addressing the emerging and contingent fiscal liabilities; raising revenues by devolving administrative power and budgets; and, improving public expenditure management. Concerning agriculture, trade, and the investment climate - promoting the commercialization of agriculture; adopting a comprehensive strategy for lagging regions, in particular the far- Western hills and mountain areas; amending the labor act to make the labor market more flexible; and, promote and enhance transport, power, and telecommunications sectors with revisions to existing laws. On public services delivery - strengthening institutions, improving civil service performance and professionalism, and, foster decentralization. Most important, social protection programs should be rationalized by evaluating their impact and cost-benefits.